Is it possible to alleviate thoracic surgery? chest tube removal before the extubation - Hazem, Zribi; Ahmed, Ben Ayed; Amina, Abdelkbir; Sarra, Maazaoui; Mahdi, Abdennadher; Taher, Mestiri; Adel, Marghli (International Surgery Journal, 2017)
Background: The ambulatory surgery (AS), is an operative management that does not require an overnight hospital stay. But, the application of AS still limited in the thoracic surgery due to the necessity of air leaking management. The aim of this study is to review our AS institutional experience by a chest drain removal before the extubation, in thoracic sympathectomy surgery. Methods: We have carried out a retrospective analysis of patients who underwent thoracic sympathectomy between November 2012 and July 2016 in the Thoracic Surgery Department of Abderrahmen MAMI University Hospital. Results: During the study period, 17 patients underwent thoracic bilateral sympathectomy. Twelve (12) females were operated versus 5 males. The mean age was 24.47 (range:17-33) years. There is no chest X-ray disorder detected during all frame times. No patient had developed a respiratory distress during the postoperative period. In addition to that, no postoperative morbidities had been detected during the follow up. All patients were satisfied about the procedure at the end of the follow up. Conclusions: The ambulatory thoracic surgery procedures can safely, and efficiency be applied if the patient is well selected. The progression on operative mini invasive techniques will increase the number of patients who can profit from an "alleviated thoracic surgery".